2023
DOI: 10.1039/d2ma00995a
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and accessing metastable phases

Abstract: Metastable forms of matter are invaluable to our everyday lives, from advancing technology to understanding biological processes, with their unique properties often offering novel functionality. Despite their importance, synthesizing metastable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In our previous work, 20 we showed that, for inter-lanthanide perovskites where both cations are lanthanides, there is a clear relationship between the energy to disorder the material and the energy to invert it -to swap the A and B cations. This leads to a broader hypothesis that this relationship might hold for other compounds and crystal structures.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous work, 20 we showed that, for inter-lanthanide perovskites where both cations are lanthanides, there is a clear relationship between the energy to disorder the material and the energy to invert it -to swap the A and B cations. This leads to a broader hypothesis that this relationship might hold for other compounds and crystal structures.…”
Section: Introductionmentioning
confidence: 91%
“…1 -with the associated space groups Pm% 3m, Fd% 3m, and Fd% 3m, respectively. In the case of perovskites, we build upon our prior work, 20 focused on inter-lanthanide perovskites that are orthorombic, with a Pnma space group. The coordination environment of the cations in these structures is very different.…”
Section: Modelsmentioning
confidence: 99%
“…41,42 Conversely, the structures above the convex hull, with negative enthalpies, indicate their existence as metastable phases. 43,44 Furthermore, different experimental techniques 45,46 have been employed, revealing that while the assessment of formation enthalpies and their convex hulls is invaluable for the discovery of stable structures, it is not necessary for obtaining stable structures in experiments. In other words, structures with high enthalpies can still be synthesized experimentally, suggesting that dynamical stability is a stronger criterion for evaluation.…”
Section: Convex Hull and Phase Diagrams Of Li-si Compoundsmentioning
confidence: 99%